POSSIBILITIES OF IMPLEMENTING ARTIFICIAL INTELLIGENCE IN WAREHOUSE MANAGEMENT - Oktambekova, Marifathon Turgunmirza qizi (Modern American Journals, 2025)
This article presents the effectiveness of introducing artificial intelligence capabilities into warehouse operations, which operations are appropriate to transfer to artificial intelligence, as well as ways to robotize and optimize operations. Analytical information is provided on artificial intelligence technologies and companies that provide them, smart warehouses, and their share in the global market.
Keywords: Artificial intelligence, AI, smart warehouses, optimization, machine learning, ML, Uzbekistan.